Mycoplasma genitalium,passenger or pathogen? - le Roux, Marie Cecilia (University of Limpopo (Medunsa), 2010)
Mycoplasma genitalium is the smallest existing self-replicating prokaryote, lacks a cell wall and has a genome consisting of only 580 kilo base pairs. It has characteristic pear/flask-like morphology with a terminal tip organelle used for attachment. Many researchers, mainly in developed countries, have investigated the role the organism plays in the aetiology of male urethritis and the majority of studies show an association between M. genitalium and male urethritis. In this study, the modified Koch’s postulates were applied to answer the question whether M. genitalium is a true pathogen, or merely a passenger, invading already inflamed or damaged cells. A total of 300 urine specimens were collected from adult males with symptoms and/or signs of urethritis and 75 from asymptomatic men. In the first study, three molecular assays; viz, a commercial conventional PCR test, a real-time PCR (q- PCR) test and a transcription mediated amplification (TMA) assay were evaluated for the detection of M. genitalium. The comparison between the assays was based on the extended gold standard concept, where a specimen was deemed positive when any two nucleic acid amplification tests were positive. In the second study, the specimens were tested for four common urethral pathogens (N. gonorrhoeae, C. trachomatis, T. vaginalis and M. genitalium) using TMA assays. Finally, the bacterial loads for M. genitalium were determined using the q-PCR assay. v All three assays tested were highly specific (98-99%) for the detection of M. genitalium. However, where q-PCR and TMA demonstrated high sensitivities (96% and 100%), the sensitivity of the conventional PCR assay was low (78%). One or more pathogens were detected in a total of 129 (43%) men with urethritis. M. genitalium was the most frequently detected pathogen in men with urethritis (129; 43%), and significantly more (p= 0.04) than in asymptomatic men (7; 9.0%). There is a strong association with M. genitalium bacterial load and clinical urethritis. Patients with urethral discharge had significantly higher M. genitalium concentrations than those with only burning on micturition (p<0.001), and the bacterial concentrations in men with symptoms and/or signs of urethritis were significantly higher than that in asymptomatic men (p=0.02). As the number of organisms increased, the severity of the symptoms increased; an indication of the role that the organism plays in disease progression. In conclusion, by applying the modified Koch postulates, it was shown that Mycoplasma genitalium is by no means a passenger, but rather an important cause of adult male urethritis that should be taken into account when making diagnosis and when designing treatment strategies.
Thesis (D Phil. (Microbiology))--2010.
Keywords: Mycoplasma genitalium